Karakteristik Leksikon Bahasa Arab di Lingkungan Pesantren: Studi Kasus di Pondok Pesantren Al-Munawwir Komplek Q Krapyak Yogyakarta - Solichah, Badi'atus (KURAS Institute, 2024)
Islamic Boarding School Al-Munawwir Krapyak, Yogyakarta, is one of the Islamic boarding schools with various focus programs. This research aims to find and describe the characteristics of Arabic lexicon variations in each program with an anthropological linguistic. The method used in this study is a combination of research and development theory in the social by Sugiyono (2022), ethnographic method by James P. Spradley (2006), and language research method by Sudaryanto (2015). There are three stages, specifically (1) the stage of data collection, which was carried out with active participation observations and unstructured interviews, then (2) the stage of data analysis, and (3) the last stage of presentation of the results of data analysis are presented informally. The results of this research show that the activities carried out by the cottage community are by the original meaning of the lexicon form itself. In addition, the lexicon in this cottage has been affected by regional languages, causing language fusion (linguistic assimilation), whose changes change the form of the language from its original language.